2006
DOI: 10.1097/01.aco.0000192816.22989.ba
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressors in obstetrics: what should we be using?

Abstract: When current evidence is considered, in the authors' opinion, phenylephrine is the vasopressor that most closely meets the criteria for the best vasopressor in obstetrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(39 citation statements)
references
References 53 publications
(34 reference statements)
0
38
1
Order By: Relevance
“…[28] that fetal umbilical pH was lower in parturients who received ephedrine than in those who received phenylephrine. Furthermore, phenylephrine has been used for quite some time as an alternative agent for the treatment of hypotension after spinal anesthesia in Cesarean sections or in cases where ephedrine was ineffective [21, 33]. Animal models with compromised fetuses suggest that phenylephrine does not increase fetal lactate concentrations [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] that fetal umbilical pH was lower in parturients who received ephedrine than in those who received phenylephrine. Furthermore, phenylephrine has been used for quite some time as an alternative agent for the treatment of hypotension after spinal anesthesia in Cesarean sections or in cases where ephedrine was ineffective [21, 33]. Animal models with compromised fetuses suggest that phenylephrine does not increase fetal lactate concentrations [16].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, ephedrine has been the vasopressor used most often in North America as it reliably prevents maternal hypotension, while mephentermine is used commonly in many Asian countries including India [11, 19]. Conversely, ephedrine has been implicated in lower umbilical pH levels, especially when used in dosages high enough to stem nausea and vomiting related to hypotension [20, 21]. Recent studies have indicated a decrease in side effects related to vasopressors, such as nausea and vomiting, and increased uteroplacental blood flow with the use of phenylephrine [17, 22].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly effective, easily titratable, and safe for the baby. [31] Norepinephrine has been shown to have similar efficacy for maintaining blood pressure, with smaller incidence of bradycardia. [32] …”
Section: Discussionmentioning
confidence: 99%
“…Among the vasopressors phenylephrine is the most effective and safe vasopressor for CS. [20] Left uterine displacement by inserting a wedge under the right lower back and physical interventions such as leg wrapping to minimize venous pooling of blood in the legs can be done. [2122]…”
Section: Discussionmentioning
confidence: 99%